Personal finance management system / Nura Lina Md Elias … [et al.] - Md Elias, Nura Lina; Yusoff, Nur Diyna; Hashim, Maryam Jameelah; Muhamad Arifin, Nur Afizah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Personal Finance Management System (PERMS) is a financial management tool designed to meet an individual filing system. It comprises both personal financial cabinet and personal financial filing. The system enables the individual to stay organized (financially) all the time. The objectives among others are to create awareness about personal finance management system, to facilitate individual’s records (personal finance documents and personal documents) organized and to ensure individual's financial planning being monitored periodically. PERMS covers seven (7) areas of personal financial planning including personal financial planning, tax planning, consumer credit, risk management, investment planning, retirement planning and estate planning. As Personal Financial Planning course (FIN533) being offered as common subject, PERMS is designed to assist teaching and learning process (as teaching tools) in the classroom when the lecturers show and articulate the system throughout the syllabus. At the end of the course, the students are expected to develop or create their own PERMS. This product is the first financial invention (personal finance management) in its kind and indirectly provides competitive advantage in financial product innovation. Even though there many furniture products in the market, but none of this merchandise specifically design to meet personal finance management system. To date, there is no identical product offered in the local or global market.